Devoted to death: Santa Muerte, the skeleton saint - Chesnut, R. Andrew (Oxford University Press, 2012)
Introduction. Blue candle for powers of insight and concentration -- Brown candle for history and origins of the cult -- White candle for beliefs and practices -- Black candle for protection and harm -- Red candle for love and passion -- Gold candle for prosperity and abundance -- Purple candle for healing -- Green candle for law and justice -- Conclusion. Seven color candle for multiple miracles